Repercussions of teleworking on motivation and job satisfaction during the pandemic in people between 18 and 65 years in Costa Rica - Ojeda Rodríguez, Celia (2023)
The article presents a correlational quantitative research, with a multivariate analysis technique, where the repercussions of teleworking on motivation and job satisfaction during the COVID-19 pandemic are analyzed, with the aim of knowing if teleworking is an influential variable. The study included 114 people from 18 to 65 years of age (M=22.8; SD=12.28), workers under the 100% virtual and bimodal modalities, who were not on disability. It is concluded that the research has a considerable sample to know that teleworking has indeed influenced motivation and job satisfaction, however, the bimodal modality was shown with a significant score, which reflects that this sample has been motivated/ to being in teleworking, because they perceive many benefits, but that face-to-face work is required to a certain degree, and in turn the research revealed that women feel more comfortable being in the face-to-face modality, otherwise in men.